Gas toolkit / Dani Asmadi Ibrahim, Noor Fatihah Zulkeply and Ashar Asrul Ros - Ibrahim, Dani Asmadi; Zulkeply, Noor Fatihah; Asrul Ros, Ashar (2020)
Mastery of chemistry concepts involves the ability to understand chemistry at all three levels; macroscopic, symbolic and submicroscopic levels. Inability to visualise the submicroscopic level (particle world) is a major problem for many chemistry students. Gas Toolkit is an education application for learning States of Matter: Gases. It enhances learning by engaging the sub-microscopic elements of the topic and making the learning experience more interactive. A usage study involving 99 students of the Matriculation Science Program was conducted. After an hour-long tutorial using the application, students achieved an average test score of 89.9% (SD 8.1%). Based on a Likert scale questionnaire 95% of the students are of the view that the Gas Toolkit has a positive impact on their learning of the topic. Similarly, the open-ended question finds out of 99 students, 90 gave positive feedbacks, 8 gave neutral or no feedback at all and only one negative feedback. Additional benefits of the toolkit are that it exposes students to various online chemistry resources and instil awareness on the utility of the digital ecosystem in the field of chemistry. In conclusion, the use of the application has successfully incorporated interactivity and sub-microscopic level learning of the topic and help improve students’ learning of Properties of Gases.